DESIGN AND CONSTRUCT UNIT TO CONTROL FLUID ENTERING SOLAR COLLECTORS DURING EFFICIENCY TESTS - Mezaal, Jawad; Alameri, Thamer (Journal of Applied Engineering Science, 2022)
This paper describes the development of an apparatus to control the fluids that enter a solar collector in experimental tests with respect to the Australian and New Zealand Standard AS/NZS 2535.1.2007. This standard explains the testing procedure, indicating that the inlet fluid should have specified temperature and flow rate uncertainties. The hardware components were constructed in the lab. A new sophisticated data acquisition system with an NI CompactDAQ was added to control the unit, and a new software application in LabVIEW was developed. The unit was operated in an open-loop to understand its behaviour as a multiple-inputs and multiple-outputs system (MIMO).  A rule of thumb tuning method was used to design the proportional-integral PI controller for the heating system.Moreover, a custom decoupler with a PI controller was developed to reduce the interactions in the MIMO. The measured steady-state responses were analysed to determine the flow rate and temperature compared with the limited boundaries. The final results show that the system could supply water to the solar collector within the accuracy requirements. Achieving the fluid's absolute temperature and flow rate within the required constraints of the published standard has proven that the developed unit can be adapted to perform solar collector testing. However, additional steps are suggested for further work to enable the unit to provide field testing.
Keywords: Solar collectors, Control system, PID controller, Decoupler, AS/NZS2535.1.2007